Aspek Hukum Pidana Pungutan Liar Terhadap Pelaku Tindak Pidana Korupsi : Studi di Kepolisian Daerah Sumatera Utara - Yosua T.R. Panjaitan; Madiasa Ablisar; Edi Yunara; Muhammad Ekaputra (Universitas Sumatera Utara, 2019)
Wild charges or abbreviated with the imposition of fees or pungli is asking for money forced by someone to another person which is the practice of crimes and breaking the law. Many people who complain and harmed by the presence of wild charges and not official just for personal interest or group. Pungli had damaged public order and cause mistrust of the community to the Government. Pungli practices within the bureaucracy caused by weak oversight and supervision among government agencies, although a number of internal and external oversight agencies has been in the form of bureaucratic culture among pungli, failed to diminish let alone eliminated. Article 1 step 5 law No. 8 of 1981 Year Book of the law of criminal procedure (CODE of CRIMINAL PROCEDURE), the investigation is a series of actions of investigators to search for and find an event that is thought to be a criminal offence in order to determine which can be or whether by way of investigation conducted under the Act. Task force saber in the response of wild charges criminal acts, then there are knowable constraints faced by UPP/task force on Clean Sweep Wild Levy, thus causing activities do not run in maximum or become less effective. barrier to coordination is the attitude of the law enforcement officers of the nonprofit agency centric i.e. each agency behaved he is the most powerful and most decisive so grow indifferent attitude towards the implementation of countermeasures of follow-up criminal saber pungli Keywords: Wild, The Levy Investigation, The Perpetrators Of The Crime Of Corruption